Multimodal pore formation in calcium phosphate cements. Issue 2 (27th October 2017) - Lodoso‐Torrecilla, Irene; van Gestel, Nicole A. P.; Diaz‐Gomez, Luis; Grosfeld, Eline‐Claire; Laperre, Kjell; Wolke, Joop G. C.; Smith, Brandon T.; Arts, Jacobus J.; Mikos, Antonios G.; Jansen, John A.; Hofmann, Sandra; van den Beucken, Jeroen J. J. P.
Abstract: Calcium phosphate cements (CPCs) are commonly used as bone substitute materials. However, their slow degradation rate and lack of macroporosity hinders new bone formation. Poly(dl ‐lactic‐ co ‐glycolic acid) (PLGA) incorporation is of great interest as, upon degradation, produces acidic by‐products that enhance CPC degradation. Yet, new bone formation is delayed until PLGA degradation occurs a few weeks after implantation. Therefore, the aim of this study was to accelerate the early stage pore formation within CPCs in vitro . With that purpose, we incorporated the water‐soluble porogen sucrose at different weight percentages (10 or 20 wt %) to CPC and CPC/PLGA composites. The results revealed that incorporation of sucrose porogens increased mass loss within the first week of in vitro degradation in groups containing sucrose compared to control groups. After week 1, a further mass loss was observed related to PLGA and CPC degradation. Macroporosity analysis confirmed that macroporosity formation is influenced by the dissolution of sucrose at an early stage and by the degradation of PLGA and CPC at a later stage. We concluded that the combination of sucrose and PLGA porogens in CPC is a promising approach to promote early stage bone tissue ingrowth and complete replacement of CPC through multimodal pore formation. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 500–509, 2018.